Comparative study on polychlorinated biphenyl sorption to activated carbon and biochar and the influence of natural organic matter. (January 2022) - Zhou, Yanmei; Miao, Dingjie; Gomez-Eyles, Jose L.; Ghosh, Upal; Bi, Mengyuan; Li, Jiuyi; Ren, Fumin
Abstract: The sorption isotherms of polychlorinated biphenyls (PCBs) on carbons (coal based activated carbon named AC and hardwood derived biochar named BC) and natural organic matter (NOM) loaded carbons were examined and carbon-water partition coefficients ( K C-W-PCB ) were calculated. The purpose was to accurately predict the effectiveness of in-situ carbon treatments on the sediment impacted with hydrophobic organic chemicals (HOCs). For 1 month sorption, AC K C-W-PCB values were significantly higher than BC, corresponding to the much larger surface area (particularly in mesopores) for AC. BC K C-W-PCB values were correlated with PCB total surface area (TSA) and octanol-water partition coefficient (log K ow ). After loading with NOM, AC adsorption to PCBs strongly reduced and the fitted Freundlich exponents ( n ) decreased with increasing NOM level. However, NOM loading slightly impacted BC sorption and exhibited an opposite effect on BC n values. It is illustrated that the sorption mechanisms are different between AC and BC thereby the influences of NOM on sorption characteristics differ vastly. As the sorption time increased from 1 month to 6 months, an increase is observed in BC sorption extent but simultaneously NOM reduction effect on BC sorption increases, implying that more accurately evaluating BC application as an in-situ sorbent amendment for HOC impacted sediment need further investigation. On the contrary, AC adsorption attenuation caused by NOM coating greatly decreases over time, encouraging AC application as a sediment amendment. Graphical abstract: Image 1 Highlights: For short term, AC carbon-water partition coefficients ( K C-W-PCB ) are higher than BC. The attenuate effect of NOM loading on AC K C-W-PCB is much stronger than on BC. With increasing time to 6months, NOM reduction effect on BC K C-W-PCB increases. But NOM depression effect on AC K C-W-PCB significantly reduces with sorption time. Different physicochemical properties of carbons result in their sorption discrepancy.